2004
DOI: 10.1021/ja0493650
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic NMR Study of the Mechanisms of Double, Triple, and Quadruple Proton and Deuteron Transfer in Cyclic Hydrogen Bonded Solids of Pyrazole Derivatives

Abstract: Using dynamic solid state 15N CPMAS NMR spectroscopy (CP = cross polarization, MAS = magic angle spinning), the kinetics of the degenerate intermolecular double and quadruple proton and deuteron transfers in the cyclic dimer of 15N labeled polycrystalline 3,5-diphenyl-4-bromopyrazole (DPBrP) and in the cyclic tetramer of 15N labeled polycrystalline 3,5-diphenylpyrazole (DPP) have been studied in a wide temperature range at different deuterium fractions in the mobile proton sites. Rate constants were measured o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
3
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 67 publications
(78 reference statements)
7
89
3
1
Order By: Relevance
“…provided that several pyrazole molecules are linked together forming cyclic structures [19][20][21][22][23]. However, although NH-pyrazoles rapidly attain the equilibrium in the gas phase (the tautomeric equilibrium constant, K T , changes monotonically with temperature), theoretical studies have shown that the transfer is not intramolecular but must involve collisions with other molecules or the walls on the instrument of measure [3, 24,25].…”
Section: Methodsmentioning
confidence: 99%
“…provided that several pyrazole molecules are linked together forming cyclic structures [19][20][21][22][23]. However, although NH-pyrazoles rapidly attain the equilibrium in the gas phase (the tautomeric equilibrium constant, K T , changes monotonically with temperature), theoretical studies have shown that the transfer is not intramolecular but must involve collisions with other molecules or the walls on the instrument of measure [3, 24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 'complex' processes are reviewed, where pre-equilibria affect the Arrhenius curves. An overview of multiple H-transfer reactions, which have been studied in our laboratory (Klein et al 2004), will be published elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogenbonded network, as determined by crystallography, shows an additional O-H·O-H bond that breaks the symmetry. The chemical shifts of the nitrogen atoms of the 1 moiety appears at -181.7 (NH) and -115.3 ppm (-N=) while in trimer 1 3 they appear at -171.3 and -96.8, 7 this difference was attributed to the replacement of N-H·N by N-H·O=C hydrogen bonds. It is important to note that no proton transfer has occurred, that is, that the tetramer is not a pyrazolium benzoate salt.…”
Section: Introductionmentioning
confidence: 96%